High Arctic biocrusts: characterization of the exopolysaccharidic matrix - Mugnai G.; Rossi F.; Mascalchi C.; Ventura S.; De Philippis R. (Polar Biology, 2020)
Biocrusts can be found in a wide array of habitats, where they provide important ecosystem services. These microbial associations are particularly important in High Arctic environments, where biocrust colonize the newly exposed barren soil after glacier retreat and significantly contribute to soil stabilization and nutrient cycling. Starting from incipient, structurally simple biolayers, they develop in complexity, increasing from the glacier terminus. Starting from a simple community structure, mainly constituted by cyanobacteria, heterotrophic bacteria and fungi immersed in a self-secreted extracellular polymeric matrix (cyanobacterial crusts), they later may recruit mosses and lichens (moss crusts and lichen crusts, respectively). The extracellular polymeric matrix protects the biocrust community from abiotic constraints, notably drought and freezing stress, from external physical harming factors, and from predation. The physicochemical characteristics of the extracellular matrix are related to several of its properties, such as its soil-stabilizing effect and water retention. We analysed the chemical (monosaccharidic composition) and macromolecular (molecular weight distribution) properties of the extracellular polymeric matrix of biocrusts with different morphologies collected in northwestern Spitsbergen, Norway. The uronic acid content and molecular weight (MW) distribution of the extracellular polysaccharidic matrices (EPMs) appeared in accordance with the developmental stages of the biocrusts. The MW distribution also showed significant differences between the samples, possibly reflecting differences in microbial enzymatic activities leading to the degradation of high-MW polymers into smaller compounds. The MW distribution profiles presented some important differences, reflecting differences in environmental conditions and, probably, the seasonal variance in microbial community composition that is known to characterize the environment examined in the present study.